Peningkatan Produktivitas Leaf Spring Jenis Minicup Tipe MMS 2230 dengan Mengurangi Pemborosan Proses Produksi Melalui Penerapan Metode Lean Manufacturing - Suparno Suparno; Agus Selamet Susanto (Universitas Katolik Parahyangan, 2021)
PT. Indospring is a manufacturing company that produces various springs for an automotive. Among those various springs, MSM 2230 type is the most produced spring at the company. The big problem in producing the spring was related with the high waste that had impact on the low productivity. The purpose of study was to analyze the waste by using the concept of lean manufacturing particularly to identify and eliminate nonvalue added activities. The study found that there were various wastes which waiting and excessive transportation were two dominant wastes with the contribution to total of wastes at 28.96% and 18.52% respectively. The appropriate tool for further analysis on wastes was selected by using value stream mapping analysis (VALSAT), and process activity mapping (PAM) was the best tool for analyzing wastes more profoundly. The use of PAM and other tools of fishbone diagram and failure mode effect analysis (FMEA) provided important information for improvement. The implementation of improvement displayed potential increase of productivity level by reducing the processing time of the spring from 113,926.83 minutes to 75,960 minutes